Progress toward a unified kJ-machine CANDY. (March 2016) - Kitagawa, Yoneyoshi; Mori, Yoshitaka; Komeda, Osamu; Hanayama, Ryohei; Ishii, Katsuhiro; Okihara, Shinichiro; Fujita, Kazuhisa; Nakayama, Suisei; Sekine, Takashi; Sato, Nakahiro; Kurita, Takashi; Kawashima, Toshiyuki; et al.
Abstract: To construct a unified experimental machine CANDY using a kJ DPSSL driver in the fast-ignition scheme, the Laser for Fast Ignition Experiment (LFEX) at Osaka is used, showing that the laser-driven ions heat the preimploded core of a deuterated polystyrene (CD) shell target from 0.8 keV to 2 keV, resulting in 5 x 10 8 DD neutrons best ever obtained in the scheme. 4-J/10-Hz DPSSL laser HAMA is for the first time applied to the CD shell implosion- core heating experiments in the fast ignition scheme to yield neutrons and also to a continuous target injection, which yields neutrons of 3 x 10 5 n/4πsr n/shot.